Analyzing Translation Errors in Japanese Language Education Students’ Thesis Abstracts using Waddington’s Method A - Ketut Gede Adi Putra Laksana; Sulis Triyono (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2025)
This study examines the translation quality of thesis abstracts written by students in the Japanese Language Education program at Universitas Pendidikan Ganesha, Indonesia. This research uses using qualitative descriptive approach that uses Waddington’s (2001) Method A of Translation Quality Assessment to evaluate the accuracy of students’ Japanese translations of Indonesian abstracts. The dataset comprises 12 texts of bilingual abstracts analyzed using a single-rating analysis approach to identify types and severity of translation errors by using a data card. Ten error types were identified, with faux sense emerging as the most frequent and severe (−23), followed by style and grammatical errors (−15). These results indicate that students still struggle with expressing ideas naturally in Japanese and often fail to fully grasp the intended meaning of the source text. The findings suggest that while students demonstrate foundational skills in academic writing, additional training in translation strategies is necessary. Implications of this study suggest that the study has demonstrated the effectiveness of Waddington's A-Method as a practical diagnostic tool for assessing students' translation skills, providing evidence-based insights for improving teaching in translation practice. It also highlights the insights for improving teaching in translation practice and highlights the need to strengthen training in genre-specific academic writing and cross-cultural transfer. Future research is recommended to explore longitudinal research in academic translation development, integrate peer and AI-assisted feedback for translation assessment and evaluation, and compare with other quality assessment models to enhance learning outcomes in translation education.